The Role of Family Support in Combating Social Disconnection - Irfani Fithria Ummul Muzayanah (Universitas Negeri Semarang, 2025)
This study examines the role of family relationships in mitigating social disconnection, specifically feelings of lacking friendships, being left out, and experiencing isolation. A logit regression analysis was employed using nationally representative data from the 2021 Indonesian Happiness Survey. The study measured three dimensions of family support: communication frequency, shared family activities, and perceived family harmony. Findings indicate that frequent communication and family togetherness significantly reduce the likelihood of experiencing loneliness. In contrast, perceived family harmony exhibited a weaker effect. These results suggest that the quantity of family interactions is more critical than their perceived quality in alleviating social disconnection. The study highlights the importance of family engagement and communication as effective strategies for combating loneliness and enhancing individual well-being.